The membrane activity of BOK involves formation of large, stable toroidal pores and is promoted by cBID. (1st February 2017) - Fernández‐Marrero, Yuniel; Bleicken, Stephanie; Das, Kushal Kumar; Bachmann, Daniel; Kaufmann, Thomas; Garcia‐Saez, Ana J.
Abstract : The BCL‐2 family members are key regulators of the intrinsic apoptotic pathway, which is defined by permeabilization of the mitochondrial outer membrane by members of the BAX‐like subfamily. BOK is classified as a BAX‐like protein; however, its (patho‐)physiological role remains largely unclear. We therefore assessed the membrane permeabilization potential of C‐terminally truncated recombinant BOK, BOK ∆C . We show that BOK ∆C can permeabilize liposomes mimicking the composition of mitochondrial outer membrane, but not of endoplasmic reticulum, forming large and stable pores over time. Importantly, pore formation was enhanced by the presence of cBID and refractory to the addition of antiapoptotic BCL‐XL . However, isolated mitochondria from Bax −/− Bak −/− cells were resistant to BOK‐induced cytochrome c release, even in the presence of cBID. Taken together, we show that BOK ∆C can permeabilize liposomes, and cooperate with cBID, but its role in directly mediating mitochondrial permeabilization is unclear and may underlie a yet to be determined negative regulation. Abstract : BAX and BAK are members of the BCL‐2 family that form pores in mitochondrial outer membranes in response to apoptotic stimuli, thereby releasing cytochrome c, which is a point of no return in apoptosis. BOK has been proposed to be a BAX‐like protein and promotes apoptosis when overexpressed, but its precise role in cell death control remains enigmatic. Fernández‐Marrero et al . now demonstrate that a C‐terminally truncated version of BOK, termed BOK∆C, forms stable pores in artificial membranes that were synergistically enhanced by the BH3‐only protein cBID. However, isolated BAX/BAK‐deficient mitochondria did not release cytochrome  c in response to BOK∆C /cBID. Therefore, although BOK has pore‐forming activity similar to its relatives, BAX and BAK, these pores are clearly distinct and further research is needed to understand their physiological function.